(untitled) (Physical Education, Health and Social Sciences, 2025)
There is a growing trend towards online and blended learning, and a need to understand how traditional communicative methodologies, such as task-based language teaching, work in a digital environment; however, it is a face-to-face, well-established method. There is limited knowledge of TBLT when implemented through online platforms such as Zoom, Google Classroom, and learning management systems; therefore, this study aims to examine the effects of TBLT on learners’ communicative competence in online ESL classrooms. The study used a quasi-experimental research design and analyzed 30 university ESL students through pre- and post-test assessments, with exposure to TBLT and online teaching. Then, we conducted semi-structured interviews with students and teachers, which were analyzed through thematic analysis. The study found that integrating Task-Based Language Teaching (TBLT) in online ESL classrooms positively impacted learners’ communicative competence. Overall, both quantitative and qualitative results suggest that TBLT can be successfully adapted to online ESL contexts, enhancing learners’ communicative skills when supported by appropriate digital tools and interactive design. It is recommended that TBLT is an effective method in ESL classrooms.